Large Eddy Simulation of a Simplifed Car Model Exposed to an Unsteady Harmonic Crosswind - Bravo, Miguel (My University, 2014)
Large Eddy Simulation (LES) is used to simulate a case where a simplified model of a car is oscillating on its vertical axis inside a wind tunnel. This is done in order to represent incoming oscillating wind. This air flow reaches the model with an angle varying between 10 and 30 degrees. The simulation is performed for three different oscillation frequencies: 1, 2 and 4 Hz. The mesh is dynamically deformed for each timestep of the simulation in order to obtain a better description on the flow than using a quasy-steady approach, such as the ability to detect hysteresis effects. Then the evolution of the overall side force coefficient and yawing moment coefficient for the model are plotted and compared to experimental data obtained in the University of Tolouse. The differences are analyzed and recommendations for future studies and simulations are made. The computational mesh used in the simulations was created with the software FAME Hexa and the simulations were run using AVL Fire.
Keywords: Strömningsmekanik; Hållbar utveckling; Transport; Fluid mechanics; Sustainable Development; Transport